GastroDigitalShirt: A smart shirt for digestion acoustics monitoring - Baronetto, Annalisa; Graf, Luisa; Fischer, Sören; Neurath, Markus; Amft, Oliver (Proceedings - International Symposium on Wearable Computers, ISWC, 2020)
We present the GastroDigitalShirt, a smart T-Shirt for capturing abdominal sounds produced during digestion. The garment prototype embeds an array of eight miniaturised microphones connected to a low-power wearable computer and is designed for long-term recording. We present the microphone integration and shirt wiring layout. With the GastroDigitalShirt we monitored the different digestion phases over six hours in four healthy participants with no prior gastro-intestinal diseases. The collected data were annotated by two independent raters to mark Bowel Sounds (BS) instances. The interrater agreement was substantial, with Cohen's Kappa of 0.7, confirming a consistent labeling approach. Overall 3046 BS instances were individually annotated. The extracted BS were structured by Hierarchical Agglomerative Clustering. The analysis highlighted the presence of 4 BS types. The results show that our prototype can capture the main BS types reported in literature.
CRIS-Team Scopus Importer:2020-11-13
Keywords: bowel sounds; smart garments; wearable sensors